2011
DOI: 10.1055/s-0031-1280824
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Image-defined Risk Factors for Surgical Complications in Patients with Abdominal Neuroblastoma

Abstract: Our findings indicate that IDRFs are useful indicators for predicting surgical risk and surgical outcome and thus should be taken into account when planning surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 11 publications
6
28
0
2
Order By: Relevance
“…We, as others, have confirmed that absence or presence of IDRF is helpful in selecting neuroblastoma patients that may benefit from primary surgery [11,16,17]. The IDRF status of the primary tumour may also be used to assess the risk of surgery in metastatic neuroblastoma [8,18].…”
Section: Discussionsupporting
confidence: 63%
“…We, as others, have confirmed that absence or presence of IDRF is helpful in selecting neuroblastoma patients that may benefit from primary surgery [11,16,17]. The IDRF status of the primary tumour may also be used to assess the risk of surgery in metastatic neuroblastoma [8,18].…”
Section: Discussionsupporting
confidence: 63%
“…We could then recommend surgery even if ''neurological'' IDRFs are still present at the preoperative assessment, arguing that their disappearance is less likely to occur. Gunther et al described the percentage of IDRFs according to tumor stage and found that 71% of patients with stage IV and 25% with stage IVs had IDRFs at diagnosis [18]. Our study, focusing on patients with at least one IDRF at diagnosis, showed that both populations (M and Ms) lost significantly more IDRFs than patients without metastases.…”
Section: Discussionmentioning
confidence: 42%
“…G€ unther et al subsequently analyzed presurgical imaging results in a series of 60 patients with abdominal neuroblastomas, focusing on IDRFs Pediatr Blood Cancer DOI 10.1002/pbc and surgical complications. Sixty percent of the patients had IDRFs and quality of resection was strongly influenced by the presence of IDRFs at diagnosis: total resection was achieved in 100% of patients with no IDRFs, whereas resection was classified R1/R0 in 18-27% of patients whose tumors encased the IVC, aorta, or SMA [18]. However, in both series the quality of resection was based only on surgical reports and not on postoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of one or more IDRF indicates the need for neoadjuvant chemotherapy. This recommendation is sustained by numerous studies showing that the presence of surgical risk factors (SRFs), now named IDRFs, is associated with an increase in intraoperative complications and/or incomplete resection . Preoperative chemotherapy is aimed at reducing tumor volume and vascularity, thus limiting bleeding and the risk of damaging vital structures surrounding the tumor …”
Section: Introductionmentioning
confidence: 99%